Rancangan Tindak Lanjut Paska Pelaksanaan Diklat di SMA Swasta Budisatrya - Fathun Khoriba; Makmur Syukri; Sri Nurjamilah Simanjuntak; Israh Madani Siregar; M. Isnain Nasution (STID Raudlatul Iman Sumenep, 2022)
The evaluation of this training program is in the form of a questionnaire that has been filled out by the training participants. As a determination of the passing of the participants will be conducted an evaluation test / exam. Assessment of the final results of the exam/test in the form of participant answer sheets will be given in the form of a different code that is useful for educators to provide effective and objective scores. After the results of the exam come out, a meeting will be held for a graduation meeting which will later determine which training participants deserve a score from the participant's activeness, attendance and final result scores. Researchers conducted and succeeded in collecting the results of the questionnaire obtained from the form of training and education carried out for several days. The results of this study use the Kickpatrick evaluation method which greatly facilitates researchers in conducting research. Evaluasi daripada program pelatihan ini berupa hasil angket yang telah diisi oleh peserta pelatihan. Sebagai penentuan lulusnya peserta akan dilakukannya tes evaluasi/ ujian. Penilaian hasil akhir ujian/ tes yang berupa lembar jawaban peserta akan diberikan berupa kode yang berbeda yang berguna untuk pendidik agar memberikan nilai yang efektif dan obyektif. Setelah hasil dari ujian tersebut keluar akan dilakukan pertemuan untuk rapat kelulusan yang nantinya untuk menentukan peserta diklat tersebut pantas mendapat nilai dari keaktifan peserta, presensi dan nilai hasil akhir. Peneliti melakukan dan berhasil mengumpulkan hasil angket yang didapat dari bentuk pelatihan dan pendidikan yang dilakukan selama beberapa hari. Hasil penelitian ini menggunakan metode evaluasi Kickpatrick yang sangat memudahkan peneliti dalam melakukan penelitian.